Early prognosis and predictor analysis for positive coronary angiography after out-of-hospital cardiac arrest (OHCA). Issue 6 (2nd November 2018) - Higny, Julien; Guédès, Antoine; Jamart, Jacques; Hanet, Claude; Gabriel, Laurence; Dangoisse, Vincent; de Meester de Ravenstein, Christophe; Schroeder, Erwin
Abstract: Background: Key predictors of survival after OHCA have been described in the literature. Current guidelines recommend emergency angiography in patients without an obvious extra-cardiac cause of arrest. However, the value of this strategy is debated. Moreover, diagnosis of acute coronary ischaemia after OHCA remains challenging, especially in patients without ST-segment elevation. Objectives: The primary objective was to identify qualitative variables associated with an increased chance of 30-d survival after OHCA. The secondary objective was to identify predictors of 30-d survival among patients with ischaemic cardiomyopathy and patients without ST-segment elevation. Afterwards, we sought to identify parameters associated with acute coronary ischaemia and positive coronary angiography in patients without ST-segment elevation. Methods: Retrospective single-centre study including 123 patients resuscitated from OHCA. Baseline characteristics, resuscitation settings and angiographic findings were analysed. Results: The predictors of 30-d survival after OHCA included witnessed cardiac arrest, haemodynamic instability and coronary angiography. Convertible cardiac rhythm, history of coronary disease and presence of at least two cardiovascular risk factors were associated with acute coronary ischaemia. Predictors for a positive angiography in patients without ST-segment elevation included history of coronary disease, gender, diabetes, dyslipidaemia and presence of at least two cardiovascular risk factors (all p  < .05). Conclusions: We identified qualitative predictors of 30-day survival after OHCA. Our findings suggest that the recognition of acute coronary ischaemia after OHCA might be improved. The identification of risk criteria may help to select the best candidates for emergency angiography.